Silver Nanoparticles for Enhancing the Efficiency of Micropropagation of Banana (Musa acuminata L.) - Samih M. Tamimi; Halima Othman (Tropical Life Sciences Research, 2023)
Silver nanoparticles (AgNPs) have numerous applications in plant biotechnology. The unique biological activities of AgNPs in reducing microbial contamination and promoting in vitro plant growth have encouraged their use in the development of novel culture systems for the in vitro cultivation of several plant species. In this study, the influence of (80 nm–100 nm) AgNPs on the micropropagation of banana was examined by incorporating AgNPs into shoot multiplication and rooting media at concentrations of 3 mg/L–15 mg/L. Biometric parameters for shoot multiplication (number of shoots/explant, shoot length and leaf surface area) and root development (number of roots/explant and root length) were analysed. In addition, shoot chlorophyll content, proline content and the possible impact of lipid peroxidation on membrane stability of plantlets were estimated. The results showed that all concentrations of AgNPs stimulated shoot growth and enhanced root development. The highest response was observed in media supplemented with 12 mg/L AgNPs. This optimal level of AgNPs caused a threefold increase in shoot growth parameter and a similar increase in root numbers/shoot and root length. Treatment with AgNPs at 12 mg/L also increased chlorophyll and proline content of shoots by 25% and 120% over control, respectively. Although the application of AgNPs increased the level of lipid peroxidation in shoots, it however, had a limited influence on membrane stability index. These results suggested that the administration of AgNPs to culture media can be effectively utilised for the enhancement of banana micropropagation with minimal toxic effects.